O trabalho em rede na intervenção das assistentes sociais dos Institutos Federais de Educação, Ciência e Tecnologia - Prada, Talita (2015)
The aim was to analyze the concept of appropriate networks in the intervention of social workers of the Federal Institutes of Education, Science and Technology to evidence the the theorical matrix that these concepts are linked and that the interests (students, Institution, Ministry of Education) the use of these concepts serve. Its relevance is in shortage, or even absence, of a critical perspective of analysis about social policy networks and the joint debate related to the network, education and the Federal Institutes. The social relevance of the research is in the reflection, understanding and questioning of the social policy networks in the education with regard to professional education, meanwhile the rapid changes occurred with the expansion of Federal Education Network over the past decade (2003 - 2013) going from one hundred forty-two institutions in 2003 to five hundred fifty-four, extending up to the end of 2014 and reflect directly on the working conditions of social workers. It was made review in the literature, in the document analysis and also field research (questionnaires with 150 social workers of institutes and conducting semi-structured interviews). The subjects of the study were social workers with more than two years of professional practice in the Federal Institutes of Brazil. Because it is a mixed research approach, the data analysis for the quality data was the content analysis. For the quantity data analysis it was made a descriptive statistics (central tendency measure and variable cross conection). The data show the profile of a qualified professional who had intensified their inclusion in the Institutes from 2009, in order to implement the National Program of Student Assistance and that the hiring social workers will tend to growth within the institution. Despite his operation, mostly likely, be linked to the Student Assistance, a significant insertion in people management and extension projects were identified. The articulation, although punctual, was placed as important for the right insurance process. With regard to the networking among professionals it as was not clear of its definition, so the group was divided between those who believed and those who did not consider to network. The network concept appropriate in the professional intervention in FI's had been linked to positivist theoretical matrix, originated mainly from Manuel Castells and that comes especially for the appropriation of discourses within the professional experience and not an assumed conception through a reflective process in ther profession's interior. Nevertheless, the failure to adopt this perspective and even its criticism has been traced by many professionals. The adoption of the concept when prioritized and thought from the perspective of the institution comes primarily meet the institutional needs and of the Ministry of Education demands such as the execution of the Internship Program, Pronatec, Thousand Women, partnerships with companies, among other programs. When thought by professionals, facing the internal and external institutional constraints, the aim was to meet the student demands for granting access to rights.